2022
DOI: 10.1101/2022.06.02.494291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmembrane proteins tetraspanin 4 and CD9 sense membrane curvature

Abstract: Multiple membrane shaping and remodelling processes are associated with tetraspanin proteins by yet unknown mechanisms. Tetraspanins constitute a family of proteins with four transmembrane domains present in high copy numbers in every cell type. Prominent examples are tetraspanin4 and CD9 that are required for the fundamental cellular processes of migrasome formation and fertilization, respectively. These proteins are enriched in curved membrane structures, such as cellular retraction fibers and oocyte microvi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Previously, we demonstrated that TSPAN4 is sensitive to membrane curvature and undergoes significant enrichment in membranes with positive membrane curvature ( 14 ). We generated giant plasma membrane vesicles (GPMVs) from HEK293T cells expressing TSPAN4-GFP and labeled them with the plasma membrane dye DiI-C12 ( Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Previously, we demonstrated that TSPAN4 is sensitive to membrane curvature and undergoes significant enrichment in membranes with positive membrane curvature ( 14 ). We generated giant plasma membrane vesicles (GPMVs) from HEK293T cells expressing TSPAN4-GFP and labeled them with the plasma membrane dye DiI-C12 ( Fig.…”
Section: Main Textmentioning
confidence: 99%
“…To compensate for the fluorescence yield difference between OG and GFP, the fluorescent intensities of water-solvated OG and GFP were measured. 42 The mole fraction of the protein in the GPMV was calculated as follows: where I microsphere OG is the intensity of the microspheres coated with liposomes containing known concentration of OG (Figure S6).…”
Section: Plasmid Preparation and Hek293t Cell Transfectionmentioning
confidence: 99%
“…Raw data have been deposited in the OSF ( https://osf.io/p47c8/?view_only=963a1c0c7a744eb8b7e57daf98e23d07 ) ( 37 ).…”
Section: Data Materials and Software Availabilitymentioning
confidence: 99%